ANALISIS PEMAHAMAN KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA UNTUK MENJADI WIRAUSAHA - Darsono, Intan Ayu Septia; Nasution, Ute Chairuz; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2017)
This study aims to determine and analyze the Analysis of Entrepreneurship Understanding of Student Interest To Become Entrepreneur (Case Study At University Students August 17, 1945 Surabaya).The result of the research shows that (1) simultaneously knowledge of entrepreneurship, personality or attitude, skill or skill have significant influence to student interest to become entrepreneur in student of Faculty of Social and Political Science and Economics Faculty Universitas 17 Agustus 1945 Surabaya; (2) partially entrepreneurship science has no significant effect on student interest to become entrepreneur, while personality or attitude, skill or skill have significant effect to student interest to become entrepreneur in student of Faculty of Social and Political Science and Economics Faculty Universitas 17 Agustus 1945 Surabaya . Personality or Attitude and Skill or Skill most dominant in influencing student interest Faculty of Social and Political Sciences and Economics Faculty University of 17 August 1945 Surabaya.Â Keywords : Entrepreneurial Sience, Personality or Attitude, Skill, and Student Interest to Become Entrepreneur